Optimization of extraction conditions for enhancing estrogenic activity of Rheum undulatum Linné using response surface methodology. Issue 11 (23rd July 2020) - Kwak, Hee Jae; Park, Seon Ju; Kim, Yun Na; Yoo, Guijae; Jeong, Eun Ju; Kim, Seung Hyun
ABSTRACT: Response surface methodology (RSM) was applied to predict optimum conditions for estrogenic activity of Rheum undulatum extract. Box–Behnken design was used to monitor the effect of ethanol concentration, extraction temperature, and extraction time. Optimum extraction conditions were predicted as 57.1%, 65.2°C, and 23.6 h. The experimental estrogenic activity was 1.90 ± 0.1, which agreed with the predicted value of 1.95. Furthermore, a main compound of R. undulatum, rhaponticin, was determined by high-performance liquid chromatography (HPLC). Therefore, these results indicate the suitability of the model employed and the success of RSM in optimizing the extraction conditions of R. undulatum for its estrogenic activity.